2018
DOI: 10.1002/ejp.1321
|View full text |Cite
|
Sign up to set email alerts
|

Altered tactile localization and spatiotemporal integration in complex regional pain syndrome patients

Abstract: Background In complex regional pain syndrome (CRPS), altered perception of the affected hand and neglect‐like symptoms of the affected body side are common features. In this study, we presented tactile stimuli to the affected hands in CRPS patients and matched healthy controls. Methods The participants’ task was to point at the perceived positions of the stimuli using a tracking device. The spatial coordinates of the perceived positions were analysed for accuracy and consistency. We also presented patterns con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…2 00 7 ; L ew is an d Mc C ab e 2 01 0 ) . Body perception disturbance encompasses elements of body schema (for example, reduced proprioceptive acuity and mislocalization of tactile stimuli) and body image disturbance (for example, the affected limb is perceived to be larger and not belonging to the body (Moseley et al 2012;Trojan et al 2019). Body schema is defined as a "non-conscious system of processes that constantly regulate posture and movement" (Gallagher 1986), and is maintained through tactile, visual and proprioceptive stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…2 00 7 ; L ew is an d Mc C ab e 2 01 0 ) . Body perception disturbance encompasses elements of body schema (for example, reduced proprioceptive acuity and mislocalization of tactile stimuli) and body image disturbance (for example, the affected limb is perceived to be larger and not belonging to the body (Moseley et al 2012;Trojan et al 2019). Body schema is defined as a "non-conscious system of processes that constantly regulate posture and movement" (Gallagher 1986), and is maintained through tactile, visual and proprioceptive stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Altered tactile localization and spatiotemporal integration have been shown in CRPSP, and evidence for changes in the cortical representation of tactile sensory stimuli support this observation. 38 , 46 Furthermore, experimental data on peripheral nerve injury show that cortical astrocytes prime the induction of spine plasticity and mirror image pain by synaptic remodeling and cortical reorganization in the primary somatosensory cortex. According to this, we suggest that similar central nervous synaptic restructuring could induce impaired CT function contralaterally in both the PHN and CRPS group and could further alter velocity-dependent pleasantness perception in other body parts, as seen on the reference side in CRPSP.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 21 , 33 35 During the chronification, reorganization in somatosensory cortices has been demonstrated. 46 Quantitative sensory testing profiles show heat or pressure hyperalgesia, indicating C-fiber dysfunction, cold hyperalgesia, DMA, and mechanical and thermal hypoesthesia. 14 …”
Section: Introductionmentioning
confidence: 99%
“…We analyzed whether localization of the middle stimulus differed between the three-stimulus sequences (illusory rabbit, time control, and location control sequences; Figure 1). We first calculated the Euclidean distance between the reported locations of the first and third stimuli and projected the reported second stimulus location onto this line (Trojan et al, 2010(Trojan et al, , 2014(Trojan et al, , 2019. Data inspection revealed that the distribution was not normal, but rather comprised a large proportion of values near 0 (see Figure S1 in Supplementary File 1), indicating a proportion of trials in which the second stimulus had been veridically perceived near its true location identical to that of the first stimulus (i.e., an illusion was not elicited; see Figure 1); absence of the illusion was more frequent in control sequences, a result that validates the experimental design.…”
Section: Higher Proportion Of Illusory Displacements In Illusion Than Control Trialsmentioning
confidence: 99%
“…The coordinates of each localization response given by participants were recoded so that data were coded as if all participants had performed all configurations with their left body side, and the AL-2s configuration with their left arm and right leg; recoding allowed pooling all participants into one analysis while discounting stimulation side. We computed the Euclidean distance between the reported locations of the first and the third stimulus and projected the second perceived stimulus on the straight line between the first and third (Trojan et al, 2010(Trojan et al, , 2014(Trojan et al, , 2019. We computed the percentage of shift of the second stimulus toward the third (see Figure 3).…”
Section: Figure 2 Stimulator Positions For A/the Single Arm (A) and B/the Arm Leg -One Side (Al-1s) Configuration When Stimulating The Lementioning
confidence: 99%